CAPACITY BUILDINGAPARATUR DESA DALAM MENINGKATKAN PELAYANAN PUBLIK DI DESA PASIR KARAG KECAMATAN KORONCONG - Topik Hidayat Topik; Natta Sanjaya (LPPM STIA Banten, 2023)
Capacity Building is a process to improve individuals, groups, organizations, communities and society to achieve the goals that have been set This study uses qualitative methods, is a study to manage and describe data and information based on facts which are then analyzed further. The number of informants in this study amounted to 12 people using purposive sampling. From the results in the field, it shows that: 1) There is a covid-19 outbreak which has resulted in the performance of both government and private activities decreasing drastically, so that activities or activities both in the public space and outside the public space have to be limited. 2). The BPD of Pasir Karag Village has not yet fully played an active role in carrying out its duties and functions, there is still a lack of experience and knowledge of the members. 3). The budget issued by the central government in fulfilling the capacity development of the village apparatus, especially in Pandeglang district is still very minimal. 4). the influence of political factors is still high which causes injustice related to information regarding aid programs and others.